The effect of social media marketing on Instagram towards purchase intention of skincare products among Youth in Klang Valley - Tauhit, Edrina Syamimi (2024)
People from different groups of ages use social media as one of the mediums to shop for skincare products especially among youth. There is a growth in product marketing that utilises social media especially on Instagram to get a higher engagement with potential customers in buying skincare products. However, some posts on Instagram that market skincare products are too good to be true resulting in Instagram users to contemplate on whether to purchase the product or just scroll through. This research will be based on the theory of reasoned action and employs a quantitative analysis where questionnaires will be distributed among youth live in Klang Valley. In this study, researchers look at the effects and the factors that contribute towards users’ purchase intention based on social media marketing. There is a positive correlation between social media marketing activities such as sponsored posts, brand pages, and skincare product reviews and the likelihood of consumers paying attention to these posts and making a purchase. The data collected is analysed by using SPSS in doing correlation and regression analysis. The findings indicate that Instagram usage increases the purchase intention among youth due to the enjoyment felt when using Instagram. This is because rewards, absorption and autonomy provide enjoyment towards youth and increase their purchase intention towards skincare products. Future research needs to be done to examine if competition to obtain popular skincare products has the same influence towards purchase intention among youth on Instagram.